2017
DOI: 10.1007/s00477-017-1450-8
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of flooding risk hotspots based on digital elevation model, calculated and historical flooding extents: the case of Ouagadougou

Abstract: Delineation of flood risk hotspots can be considered as one of the first steps in an integrated methodology for urban flood risk management and mitigation. This paper presents a step-by-step methodology in a GISbased framework for identifying flooding risk hotspots for residential buildings. This is done by overlaying a map of potentially flood-prone areas [estimated through the topographic wetness index (TWI)], a map of residential areas [extracted from a city-wide assessment of urban morphology types (UMT)],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 25 publications
(23 reference statements)
0
44
0
Order By: Relevance
“…In this framework, the research has recently shown that the delineation of flood-prone areas can be carried out using simplified methods that rely on basin geomorphologic features (e.g., Nardi et al 2006;Manfreda et al 2011Manfreda et al , 2014aDegiorgis et al 2012;Jalayer et al 2014;De Risi et al 2014;Papaioannou et al 2014). Such innovative procedures may provide a preliminary delineation of the flood-prone areas useful for the planning of numerical analyses, and for insurance companies that have a growing interest toward the identification of the assets and population at risk.…”
Section: Introductionmentioning
confidence: 99%
“…In this framework, the research has recently shown that the delineation of flood-prone areas can be carried out using simplified methods that rely on basin geomorphologic features (e.g., Nardi et al 2006;Manfreda et al 2011Manfreda et al , 2014aDegiorgis et al 2012;Jalayer et al 2014;De Risi et al 2014;Papaioannou et al 2014). Such innovative procedures may provide a preliminary delineation of the flood-prone areas useful for the planning of numerical analyses, and for insurance companies that have a growing interest toward the identification of the assets and population at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, the systematic engagement of a wide range of stakeholders in indicator selection as well as in discussions on how to plan for climate change adaptation was also a new and innovative method (Nyed and Herslund 2013) The project 'cocreated' data and learning for the use of local authorities in the years to come-data which are relatively simple to update, e.g., through vulnerability mapping which combined different data types and sets in GIS layers. Fifth, a probabilistic flood hot spot methodology was developed and applied to several case study cities, providing a method for flood risk screening which has strong potential for application in other Sub-Saharan urban contexts (Jalayer et al 2014b;De Risi et al 2014). Sixth, the integration of the different assessment methods was attempted through multiple studies undertaken at the same case study sites and involving experts in engineering, social science, climate science, geography, ecology and urban and green infrastructure planning.…”
Section: Innovation and Future Researchmentioning
confidence: 99%
“…De Risi et al (2014) studied DEM as well as a probabilistic framework for Ouagadougou, Burkina Faso, Africa for the year 2009. They concluded that the Bayesian updating procedure was useful for computing the topographic wetness index (TWI) threshold.…”
Section: Literature Reviewmentioning
confidence: 99%